2021
DOI: 10.1108/jkm-08-2020-0590
|View full text |Cite
|
Sign up to set email alerts
|

The impact of knowledge flows on asset specificity from the perspective of open innovation

Abstract: Purpose This study aims to examine how different modes of knowledge flows affect the changes of asset specificity and how ownership control moderates the relationship between knowledge flows and asset specificity in the open innovation paradigm. Design/methodology/approach This paper selects information technology outsourcing as the research base. It uses the feasible weighted least squares modeling method for its analysis and has collected the data from 2,369 research and development contracts of multinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 116 publications
(138 reference statements)
0
5
0
Order By: Relevance
“…First, firms always struggle to develop strategies to increase contributors’ creative performance and sustain it over time. Online team collaboration has been considered as one such strategy because it can not only lower the barriers of innovation but also use the “wisdom of crowds” to make high-quality contributions (Daniel et al , 2013; Zheng et al , 2022). Our research suggests a unique potential benefit of online team collaboration: contributors can learn new knowledge and expertise from others through the collaboration process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, firms always struggle to develop strategies to increase contributors’ creative performance and sustain it over time. Online team collaboration has been considered as one such strategy because it can not only lower the barriers of innovation but also use the “wisdom of crowds” to make high-quality contributions (Daniel et al , 2013; Zheng et al , 2022). Our research suggests a unique potential benefit of online team collaboration: contributors can learn new knowledge and expertise from others through the collaboration process.…”
Section: Discussionmentioning
confidence: 99%
“…For example, online discussion forums in the open-source software community function as the platforms for contributors to report bugs, exchange technical information and propose code modifications (Sun et al , 2020). These social interactions enable effective knowledge transfer across contributors and improve the efficiency to learn from others (Zheng et al , 2022). However, how and when these knowledge and expertise learned from others affect contributors’ creative performance in the context of open innovation communities is still unclear and needs further examination.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Since Williamson (1985) first defined asset specificity, several researchers have attempted to highlight the redefinition of the concept through their own interpretations. Firms maintain higher asset specificity to maximize the efficiency of knowledge flows, which helps them improve their innovation capabilities and market performance (Zheng et al , 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cao et al,(2021), asserted that employees can utilize knowledge more effectively if they are capable of acquiring and assimilating the knowledge. On the other hand, Zheng et al (2021) pointed out that the concept of KM, a concept based on knowledge flows, is closely related to the concept of knowledge flows in open innovation. Accordingly, we hypothesise that knowledge flows have a positive impact on open innovation.…”
Section: Km Mediating Between Hpws and Open Innovationmentioning
confidence: 99%
“…By developing a proposal research model, this study contributes to addressing these issues by examining the potential mechanisms that mediate KM process between open innovation and high-involvement HRM practices As a result of this study, the mediating effect of KM was verified and AMO practices were found to be an optimal choice for firms, particularly in developing countries such as Jordan, for fostering open innovation directly or indirectly through its influence onKM and KWP( Bin Mahfodh et al, 2020). There is no doubt that HPWS have huge benefits and are important to innovation(Gemici and Zehir,2019), however, there are very few studies investigating how HPWS can improve open innovation(Abualoush et al, 2022) Jiao et al (2021). stated that "several scholars proposed the relationship between HRM and KM capability based on the literature.…”
mentioning
confidence: 99%